The Influence of Transformational Leadership and OCB on Teachers' Professional Commitment in Early Childhood Education Institutions in Serpong, Indonesia - Yulita Pujilestari; Abd. Chaidir Marasabessy; Ichwani Siti Utami (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the influence of transformational leadership and organizational citizenship behavior on teachers' professional commitment. The research method uses quantitative research with survey techniques. A total of 75 teachers spread across 23 active Early Childhood Education institutions in Serpong District, South Tangerang City. Sampling using total sampling technique and data collection using closed questionnaires that have been tested for validity and reliability, covering three main variables, namely transformational leadership, organizational citizenship behavior, and teachers' professional commitment. Data analysis using multiple linear regression. The research findings show that transformational leadership and organizational citizenship behavior simultaneously have a significant and positive effect on teachers' professional commitment. The analysis model shows very high explanatory power, with an R² value of 0.996, indicating that the two independent variables can explain 99.6% of the variation in the professional commitment variable. No multicollinearity problems were found, so the regression model is declared valid. These findings underline the important role of transformational leadership and organizational citizenship behavior in increasing teachers' commitment to early childhood education, providing strategic implications for the development of leadership and organizational culture in educational environments.